Manajemen Mitigasi Penanggulangan Bencana Banjir Oleh Badan Penanggulangan Bencana Daerah (BPBD) Kota Cilegon di Kecamatan Ciwandan - Syifa Nurillah; Delly Maulana; Budi Hasanah (Universitas Serang Raya, 2022)
Cilegon City is an area that is prone to various types of disasters, including natural disasters. Natural disasters are natural phenomena that can result in environmental damage and destruction which in the end can cause casualties, property losses and damage to developments that have been built so far. Cilegon City is an area that is prone to disasters, one of which is the Ciwandan District. This area has the potential for complex natural disasters. Not only the threat of flooding at the end of every year, but this industrial city is also prone to hurricane and industrial disasters. Based on the records of the Cilegon Regional Disaster Management Agency (BPBD) for the last two years, the threat of flooding and tornadoes is in the first place. This study uses a descriptive qualitative approach. That is with the aim of knowing how to implement the mitigation management function carried out by the regional disaster management agency (BPBD) in dealing with flood hazards. The results showed that the disaster management planning process through the mitigation management approach in Ciwandan District had been implemented even though there were stages that were not maximized.